Ujian Akhir Madrasah Berbasis Android: Inovasi Mengatasi Minimnya Media Komputer MIN 1 Lebong - Yunsi Reva Agustina; Fakhruddin Fakhruddin; Muhammad Istan (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
This study sought to find a depiction of innovation made by the principal and teachers at MIN 1 Lebong concerning the madrasah’s final exams academic year 2018/2019, amid the lack of media, by replacing the Computer-based madrasah’s final exams (UAMBK) to Android-based madrasah’s final exams (UAMBA). Thus, it called for an in-depth study to see its implementation. This study employed a qualitative approach. The data were collected through observation, interview, and documentation techniques, and the data were subsequently analyzed using Miles, Haberman, and Saldana’ version of analysis, namely data reduction, data presentation, and drawing conclusion. This study concluded that the implementation of Android-based final exams, or the so-called UAMBA, was considered quite effective and efficient because it had several advantages including saving more budgets, being able to minimize the delay of UAM test packages, minimizing the occurrence of cheating during exams, making it easier for students, and making the exam results capably known quickly because the manual implementation of national exams was costly, wherein it demanded budgets for printing national exam packages and distributing those national exam packages.